3x*3x*3x=4x-9

Simple and best practice solution for 3x*3x*3x=4x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x*3x*3x=4x-9 equation:



3x*3x*3x=4x-9
We move all terms to the left:
3x*3x*3x-(4x-9)=0
Wy multiply elements
27x^3*3-(4x-9)=0
We get rid of parentheses
27x^3*3-4x+9=0
We do not support expression: x^3

See similar equations:

| -30+6n=4(n-7) | | -6(v+2)+3v+6=7v+6 | | 4(x-2)+6=2x+2(-3+x) | | r-0.80=1.70 | | 2m–2=2 | | -31/6=7/3+p | | 3x–x+1=17 | | -9=3(b+4) | | 0.10(y-2)+0.02y=0.20y-0.6 | | 91-7h=854 | | 2a-1=3(a+7) | | F(x)=-2/7x | | -2=t/6 | | 3/8=27/m | | x+x+6+6=6x | | 6(3n-4)=(6n+4)+6 | | 5x^2+16x=11x–3x^2 | | 14+8y=6+-2y | | -4(5-3z)=6z+28 | | -2(2x+5)=3x-7+7x | | 6(3n-4)=(6n+4)=6 | | 5x2+16x=11x–3x2 | | 2+16.5x=4+7.5x | | 4(u+1)=9u+99 | | 9x-2(x-9)=7(x+1)+6 | | j/9-3=-11 | | 1v=-21 | | 46=37x | | 73/18=-2/3n+3/2 | | 5/6=e/36 | | -4(t-1)+8t=9t-6 | | -2x+5x-6=3(x-6)-0 |

Equations solver categories